(untitled) (Palimpsesto, 2019)
We propose to identify the political-intellectual trajectory of the historian Luis Vitale (1927-2010), through a biography that recognizes historical processes, debates and relevant intellectual networks, considering his experience as another manifestation within the Latin Americanist thought of the second half of the 20th century. We addressed their identity, formation and intellectual ties in Argentina until 1954. Then in Chile within the labor movement, until the military coup of 1973. The exile has been reconstructed by means of its correspondence, ending with the return to the country and the collaboration with intellectuals from the social movements of a new type. The result is a brief biography that aims to contribute to the enhancement of your personal file located at the University of Santiago.